2015
DOI: 10.3109/0284186x.2015.1063782
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the dominant prostate cancer focal lesion using image analysis and planning of a simultaneous integrated stereotactic boost

Abstract: These preliminary results demonstrate the potential of this image analysis method for reliably mapping dominant focal disease within the prostate from MR images onto planning CT images. Significant dose escalation using a simultaneous integrated SABR boost was achieved in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The imaging fusion issue and its clinical implications have already been studied in literature. 10 Other patients had to be excluded due to mp-MRI findings not matching the inclusion criteria (e.g. cT3 tumors) or to an unsatisfactory urinary flow.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging fusion issue and its clinical implications have already been studied in literature. 10 Other patients had to be excluded due to mp-MRI findings not matching the inclusion criteria (e.g. cT3 tumors) or to an unsatisfactory urinary flow.…”
Section: Discussionmentioning
confidence: 99%
“…Two out of 3 cases for V 30.8 Gy > 1 cc were also exceeding range within 2 cc. We had to point out that the other study groups used more generous OAR constraint than the present study; rectal D max ranged from 36 to 38 Gy (The present study, 35 Gy), rectal V 32.3 -36 Gy < 1 cc (The present study, V 30.8 Gy < 1 cc), and bladder D max 41.8 Gy (The present study, 38.5 Gy), V 38 Gy < 1 cc or V 37 Gy < 10 cc (The present study, V 35.7 Gy < 1 cc) [15][16][17] . Kim et al reported the dosimetric predictors of rectal tolerance observed in a phase 1-2 trial of dose-escalated SBRT with 45, 47.5, and 50 Gy in 5 fractions to the whole prostate 18 .…”
Section: Discussionmentioning
confidence: 43%
“…While the majority of these efforts have been realized using intensity-modulated radiation therapy (7, 9, 11, 3133), studies have also included dose-escalation using brachytherapy with biologically equivalent doses of around 200 Gy to the DIL (6, 3436), and more recently with stereotactic body radiotherapy using a simultaneous integrated boost technique (14, 32, 37, 38).…”
Section: Discussionmentioning
confidence: 99%